VALIDITY OF INFOGRAPHIC LEARNING MEDIA THEME OF GREEN GROWTH IN TRAINING CRITICAL THINKING SKILLS - Elfira Mawardani; Mudmainah Vitasari; Liska Berlian (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
Infographic learning media is one of the intermediaries in the learning process made with graphic design, namely canvas. This media infographic is used to give Canva learning materials to students to achieve a learning goal. This study aims to develop learning media infographics and determine the level of validity. The media used is research and development or Research and Development adapted from the Borg and Gall development model, consisting of three stages, namely Research and Information Collecting, Planning, and Preliminary Form of Product. The research instruments used in this study were interview sheets and validation sheets. This study indicates that the level of validity of the infographic learning media on the theme of the green growth in training critical thinking skills of seventh-grade students obtained an average value of 78.94% with a valid category so that infographic learning media can be used in the learning process.